Teoria de médio alcance para o diagnóstico de enfermagem imagem corporal conturbada em pessoas que sofreram amputação - Moreira, Janaína Calisto (2025)
Disrupted Body Image is defined by NANDA-I as “Negative mental picture of one´s physical self”. In the context of people who have suffered amputation, it is possible to improve the diagnosis to specifically serve this population. Thus, this study aimed to develop a MiddleRange Theory that identifies and defines the elements and clinical processes that lead to the establishment of the nursing diagnosis Disrupted Body Image in people who have suffered amputation. Thus, this research is a Theoretical Validation study, which was developed in three stages: Systematic review of etiology and risk, Systematic review of diagnostic accuracy and the development of the Middle-Range Theory itself. In addition, the Roy Adaptation Model was used to analyze the assumptions related to the diagnosis in question. The review of etiology and risk was conducted based on chapter seven of the JBI Evidence Synthesis Manual. The review was carried out in five databases, and used the PEO mnemonic strategy for the question on etiology and risk: "What are the etiological factors related to the nursing diagnosis Disrupted Body Image or consistent with this phenomenon in people who have undergone amputation?". The protocol for this review was registered on the PROSPERO platform on 07/26/2023 (CRD42023442860). For the review of diagnostic accuracy, the Cochrane Handbook for Systematic Reviews of Diagnostic Test Accuracy was used. This review was conducted in five databases and used the PIT mnemonic strategy, with the following question: "What are the clinical indicators related to the nursing diagnosis Disrupted Body Image or consistent with this phenomenon in people who have undergone amputation?". The protocol was registered on PROSPERO on 04/06/2024 (CRD42024527391). For the construction of the Middle-Range Theory itself, six steps were followed: definition of the approach for constructing the MiddleRange Theory; definition of the conceptual models to be analyzed; definition of key concepts; development of a pictorial diagram; construction of propositions; and establishment of causal relationships and evidence for practice. The Middle-Range Theory developed resulted in the identification of 26 etiological factors, the most prevalent in the literature being: Female gender, Amputation due to trauma, Non-use of prosthesis, Lower level of satisfaction with the prosthesis, Minimally active individuals in terms of physical activity/non-practitioners of exercise and sports, and Phantom limb pain; and 20 clinical indicators, the most prevalent in the literature being: Interference of pain in usual activities, Lower level of psychosocial adjustment, Anxiety, Depression, Low self-esteem, Social restriction/Activity restriction, Low quality of life, and Sexual dysfunction. From the results presented, it was possible to develop a diagnostic structure aimed at people who have suffered amputation, which included 49 defining characteristics, 25 related factors, 11 at risk population and 13 associated conditions with the diagnosis of Disrupted Body Image, which will contribute to the standardization of nursing language, in the construction of studies that bring theory and practice closer together and in obtaining new scientific evidence that may help in dealing with the diagnosis in individuals with amputation.